"So I am stuck, but it´s OK": residential reasoning and housing decision-making of low-income older adults with disabilities in Baltimore, Maryland. Issue 1 (2nd January 2021) - Granbom, Marianne; Nkimbeng, Manka; Roberts, Laken C.; Gitlin, Laura N.; Taylor, Janiece L.; Szanton, Sarah L.
ABSTRACT: Housing preferences and housing decision-making in later life are critical aspects of aging in place, which is a public health priority in many Western countries. However, few studies have examined the economic, social, and health factors that guide older adults' preferences and decisions about where to live, and even less so among older adults with low income or disabilities who may face greater barriers to aging in place. We sought to understand what housing decision-making and residential reasoning means for low-income older adult homeowners in Baltimore, Maryland. Using a grounded theory approach, we interviewed 12 older adults in June 2017 and February 2018. Our findings revealed how the strong desire to age in place turned into the realization that they had to age in place due to limited resources and options. The overarching category "shifting between wanting to age in place and having to age in place" was influenced by family needs, being a homeowner, the neighborhood, and coping at home. In conclusion, for low-income older adults with disabilities, it is important to acknowledge that sometimes aging in place may be equivalent to being stuck in place.